Demand vs. supply driven innovations: US and Swedish experiences in academic entrepreneurship - Brent Goldfarb; Magnus Henrekson; Nathan Rosenberg (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
Measured by per-capita publication measures, Sweden is an academic powerhouse. Hence, its inability to commercialize on these accomplishments is a puzzle. This paper attributes this failure to the top-down nature of Swedish policies aimed at commercializing these innovations as well as an academic environment that discourages academics from actively participating in the commercialization of their ideas. This sits in stark contrast to the US institutional setting that is characterized by competition between universities for research funds and research personnel, which in turn has led to significant academic freedoms to interact with industry, particularly by founding new firms. We conclude that the technocratic, supply-driven nature of attempts to exploit academic output in Sweden has been markedly less successful than the demand-driven market institutions in the US.
Keywords: J24; O31; O32; O57; 330; Academic entrepreneurship; Innovation; R&D; Spin-off firms; Technology transfer; University-industry relations; Universities and business formation